2009
DOI: 10.1021/jp9036765
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Lamellar Mesostructure of Nanocrystalline PbSO4 Prepared by Hydrothermal Treatment

Abstract: A lamellar PbSO 4 mesophase with well-crystallized walls was synthesized using sodium dodecyl sulfate (SDS) as a template and bis [3-(triethoxysilyl)propyl]tetrasulfide (TESPTS) as a structure-stabilizing agent through hydrothermal treatment method. The obtained layered mesostructure was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and high-resolution TEM (HRTEM), energy-dispersive X-ray spectroscopy (EDS), and IR spectrum. The photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The low emission intensity of the PbSO 4 clusters/polymer, at about 350 nm (λ exc = 270 nm), is that which was expected for these structures (Figure S3b,c, Supporting Information). [ 16a,19 ] The 1 H‐NMR spectrum of the PbSO 4 cluster showed the presence of mostly oleylamine together with some oleic acid (see comment added to Figure S6 in the Supporting Information), while that of the supernatant showed the presence of CHMAHS (spectrum not shown), thus demonstrating that its role was mainly to facilitate the formation of suitable lead clusters for the assembly of the UCNPs within the lead cluster. These PbSO 4 clusters were used to synthesize all the assemblies described from here on.…”
Section: Resultsmentioning
confidence: 99%
“…The low emission intensity of the PbSO 4 clusters/polymer, at about 350 nm (λ exc = 270 nm), is that which was expected for these structures (Figure S3b,c, Supporting Information). [ 16a,19 ] The 1 H‐NMR spectrum of the PbSO 4 cluster showed the presence of mostly oleylamine together with some oleic acid (see comment added to Figure S6 in the Supporting Information), while that of the supernatant showed the presence of CHMAHS (spectrum not shown), thus demonstrating that its role was mainly to facilitate the formation of suitable lead clusters for the assembly of the UCNPs within the lead cluster. These PbSO 4 clusters were used to synthesize all the assemblies described from here on.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this hypothesis, the magnetic Fe 3 O 4 @C nanoparticles were employed for the absorption of Pb 2+ , Hg 2+ , Cd 2+ ions. The –OH absorption band shifted to 3430 cm –1 , and the signals at 1206 and 1123 cm –1 for the –SO 3 H group disappeared (see Figure 5, b–d and Supporting Information, Figure S1), which indicates that the sulfonic and carboxylic acid groups were transformed into sulfonate and carboxylate groups,43,44 respectively. These observations suggested that the as‐obtained magnetic Fe 3 O 4 @C nanoparticles could be used as an adsorbent for the capture of heavy metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…The bilamellar phase of Ag‐MOA superclusters could be attributed to the coexistence of two included angles in MOA‐Ag n ‐MOA (Scheme d). They are both metastable phases in the superclusters …”
Section: Methodsmentioning
confidence: 99%
“…They are both metastable phases in the superclusters. [27,28] The procedure for assembling can be scaled up readily as shown in Figure S13 (Supporting Information). Figure 3a represents a specimen of pressed Ag-MPA superclusters (1.3 × 0.4 cm) that is mechanically robust in opposition to typical fragile and unstable silver-based nanomaterials.…”
Section: Self-assemblymentioning
confidence: 99%